A blended learning approach in higher education: A case study from surveying education - El-Mowafy, Ahmed; Kuhn, Michael; Snow, Tony (Teaching and Learning Forum 2013, 2013)
The development of a blended learning approach to enhance surveying education is discussed in this paper. The need for such learning strategy is first investigated based on a major review of the Surveying course including analysis of its content, benchmarking with key national/international universities, and various surveys to key stake holders and recent graduates. Appropriate blended learning methods and tools that couple learning theoretical principles and developing technical skills are discussed including using learning management systems, flip teaching, collaborative learning, simulation based e-learning, peer- and self-assessment and e-portfolios. Two blended learning tools that have been developed for surveying units are presented as examples. The first is an online interactive virtual simulation tool for levelling, one of the key basic tasks in surveying. The second is an e-assessment digital marking, moderation and feedback module. The e-learning and e-assessment tools have been incorporated for three years into several surveying units at Curtin University. Surveys of students showed that the majority of students found the interactive simulation tool useful and contributes to improving their understanding of the computations. Students also found the digital marking rubric helpful in assisting their understanding of practical task requirements, in improving their performance, and in helping them to focus on the objectives of each activity. The paper concludes with a discussion on developing generic skills through authentic learning in surveying education.